The effect of market risk on returns: Case of banking in Indonesia - Dhea Modeong; Ricky Wati; Jeine Ante; Efrianto Tadung (Yayasan Widyantara Nawasena Raharja, 2022)
The banking industries are a sector that play important role to support national development and national economy. During Covid-19 pandemic, most of market in the world include Indonesia has urgent circumstances. The objective of this study is to examine whether the Covid-19 pandemic has bad impact on returns of banking industries. The results of regression over January 3, 2020, to December 30, 2021 show that there is positive relationship for risk-return of BBNI and BBRI. Those results imply that Covid-19 pandemic does not have significant effect on returns for those banks. It also means that most investors feel safe for those banks financial performance.